2015
DOI: 10.1353/jaas.2015.0029
|View full text |Cite
|
Sign up to set email alerts
|

A Portrait of Refugees from Burma/Myanmar and Bhutan in the United States

Abstract: Who are Burmese and Bhutanese Americans? What caused their migration? While national data shows Bhutanese and Burmese constituting a large proportion of refugees entering the United States in recent years, they, however, remain largely invisible in the current national discourse on Asian American socioeconomic outcomes. This article addresses this gap by providing a historical and demographic portrait of the Burmese and Bhutanese communities—specifically addressing their social, economic, political, and educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…Bhutanese refugees began arriving in the United States in 2007, following a UNHCR decision to resettle those living in Nepalese refugee camps (Trieu and Vang 2015). Many are descendants of ethnic Lhotshampas-Nepalese migrants settling in southern Bhutan.…”
Section: Bhutanesementioning
confidence: 99%
See 2 more Smart Citations
“…Bhutanese refugees began arriving in the United States in 2007, following a UNHCR decision to resettle those living in Nepalese refugee camps (Trieu and Vang 2015). Many are descendants of ethnic Lhotshampas-Nepalese migrants settling in southern Bhutan.…”
Section: Bhutanesementioning
confidence: 99%
“…Between 1990 and 1993, about a hundred thousand Nepalesespeaking Bhutanese fled Bhutan for refugee camps in eastern Nepal. They languished in these camps for two decades, unable to repatriate to Bhutan or to receive formal refugee status from the UNHCR (Trieu and Vang 2015). Following a change in policy by UNHCR, a total of 5,244 Bhutanese refugees arrived in the United States from these refugee camps in 2008 (Vang et al 2014;Capps et al 2015).…”
Section: Bhutanesementioning
confidence: 99%
See 1 more Smart Citation
“…The acceptance of Burmese refugees for resettlement in North America, Australia, and Europe signaled that donor countries considered it unlikely that any resolution to Burma's complex state-society and armed conflicts would be achieved soon (South, 2011). The peak year for Burmese refugees entering the U.S. was in 2009, with 18,202 arrivals (Trieu & Vang, 2015) and the largest Burmese populations are resettled in the southern and western states of the U.S.; they are young populations, with the majority (67 percent) under forty years of age. Among the student population, Burmese students have the highest school dropout rate (44 percent) of all major Asian ethnic groups; furthermore, 33 percent of Burmese refugees live below the poverty line (Community of Contrasts, 2011), adding to the urgency of understanding the educational barriers of this group in order to inform the practices of school systems and their personnel.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Many of these refugees face significant challenges as they transition into a new life in the U. S., including poor English language skills and little education or work experience. A study showed that Burmese had the highest high school dropout rate (44%) among all major Asian ethnic groups and 33% of Burmese were living below the poverty line [23]. Religious beliefs, practices, and institutions play a large role in adaptions, community building, and cultural navigations for refugees [22].…”
Section: Introductionmentioning
confidence: 99%